EphA4-ADAM10 Interplay Patterns the Cochlear Sensory Epithelium through Local Disruption of Adherens Junctions - Defourny, Jean; Peuckert, Christiane; Kullander, Klas; Malgrange, Brigitte (iScience, 2019)
The cochlear sensory epithelium contains a functionally important triangular fluid-filled space between adjacent pillar cells referred to as the tunnel of Corti. However, the molecular mechanisms leading to local cell-cell separation during development remain elusive. Here we show that EphA4 associates with ADAM10 to promote the destruction of E-cadherin-based adhesions between adjacent pillar cells. These cells fail to separate from each other, and E-cadherin abnormally persists at the pillar cell junction in EphA4 forward-signaling-deficient mice, as well as in the presence of ADAM10 inhibitor. Using immunolabeling and an in situ proximity ligation assay, we found that EphA4 forms a complex with E-cadherin and its sheddase ADAM10, which could be activated by ephrin-B2 across the pillar cell junction to trigger the cleavage of E-cadherin. Altogether, our findings provide a new molecular insight into the regulation of adherens junctions, which might be extended to a variety of physiological or pathological processes. [Display omitted] •EphA4 and ephrin-B2 are co-expressed on both sides of the pillar cell junction•Pillar cells fail to separate from each other in the absence of EphA4 signaling•EphA4 forms a complex with E-cadherin and ADAM10 at the pillar cell junction•E-cadherin inhibition rescues the pillar cell detachment in the absence of EphA4 Physiology; Cell Biology; Developmental Biology